2021
DOI: 10.2174/1573396316666200430084825
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Alopecia Areata

Abstract: Background: Alopecia areata (AA) is a non-scarring hair loss disorder of autoimmune etiology. Objective: To familiarize physicians with the clinical presentation, diagnosis, evaluation, and management of pediatric alopecia areata. Methods: The search term "Alopecia areata" was entered into a Pubmed search. A narrow scope was applied to the categories of "epidemiology", "clinical diagnosis", "investigations", "comorbidities", and "treatment". Meta-analyses, randomized controlled trials, clinical trials, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 95 publications
0
11
0
4
Order By: Relevance
“…Но некоторые факторы могут приводить к потере иммунной привилегии: у детей таковыми являются, как правило, влияние генетических факторов, наличие атопии, аутоиммунные заболевания [5], вследствие чего определённые экспрессирующиеся аутоантигены, в частности трихогиалин и родственный тирозиназе белок 2, распознаются Т-лимфоцитами [21]. В итоге они (по большей части это CD3+CD8+ Т-лимфоциты [22], значительную роль играют также NKG2D+ клетки [23,24]) пролиферируют, мигрируют к фолликулу и инфильтрируют окружающую его дерму [25]. Иммунные клетки начинают продуцировать интерферон-γ (ИНФ-γ), что в свою очередь увеличивает экспрессию MICA (лиганд NKG2D), CXCL10 и MHC I через JAK-STAT каскады, а также продукцию интерлейкина-15 (ИЛ-15) [26].…”
Section: современные представления о патогенезеunclassified
See 1 more Smart Citation
“…Но некоторые факторы могут приводить к потере иммунной привилегии: у детей таковыми являются, как правило, влияние генетических факторов, наличие атопии, аутоиммунные заболевания [5], вследствие чего определённые экспрессирующиеся аутоантигены, в частности трихогиалин и родственный тирозиназе белок 2, распознаются Т-лимфоцитами [21]. В итоге они (по большей части это CD3+CD8+ Т-лимфоциты [22], значительную роль играют также NKG2D+ клетки [23,24]) пролиферируют, мигрируют к фолликулу и инфильтрируют окружающую его дерму [25]. Иммунные клетки начинают продуцировать интерферон-γ (ИНФ-γ), что в свою очередь увеличивает экспрессию MICA (лиганд NKG2D), CXCL10 и MHC I через JAK-STAT каскады, а также продукцию интерлейкина-15 (ИЛ-15) [26].…”
Section: современные представления о патогенезеunclassified
“…Вовлечение в процесс ногтей наблюдается в 10-50% случаев [25], при этом изменения ногтей ассоциируются с более тяжёлым течением ГА у детей, и у таких пациентов выше распространённость офиазиса [34].…”
Section: особенности клинических проявлений гнёздной алопеции детског...unclassified
“…Se caracteriza por producir áreas circulares u ovaladas de pérdida de pelo no cicatricial, de fondo limpio, muy bien delimitadas en el cuero cabelludo, las cejas, las pestañas o en cualquier lugar donde haya pelo. 2 El lupus eritematoso sistémico es una enfermedad autoinmune crónica, multisistémica, d e c u r s o v a r i a b l e . E s m á s f r e c u e n t e e n mujeres, sobre todo en edad reproductiva y menos frecuente en la infancia.…”
Section: Alopecia Por Sífilisunclassified
“…Patients will often present with patchy, non-scarring hair loss generally affecting the scalp. [1][2][3] The role of hair in human societies is primarily psycho-social. This was corroborated by a systematic review with metaanalysis 4 that concluded that patients with AA experience significant impairment in health-related quality of life (HRQoL), especially in the area of mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing AA can be made on the basis of the history and clinical findings. Patients will often present with patchy, non‐scarring hair loss generally affecting the scalp 1–3 …”
Section: Introductionmentioning
confidence: 99%